2018
DOI: 10.1155/2018/4010629
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Thymoquinone in Glioblastoma Treatment: Targeting Major Gliomagenesis Signaling Pathways

Abstract: Glioblastoma multiforme (GBM) is one of the most devastating brain tumors with median survival of one year and presents unique challenges to therapy because of its aggressive behavior. Current treatment strategy involves surgery, radiotherapy, immunotherapy, and adjuvant chemotherapy even though optimal management requires a multidisciplinary approach and knowledge of potential complications from both the disease and its treatment. Thymoquinone (TQ), the main bioactive component of Nigella sativa L., has exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 208 publications
(220 reference statements)
0
27
0
Order By: Relevance
“…The study by Pećina-Šlaus et al indicated the increased expression of transcriptional factors TCF-1 and LEF-1 to be characteristic for malignant gliomas [23]. Other signaling pathways, including receptor tyrosine kinase (RTK), epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor A (PDGFRA), fibroblast growth factor receptor 1 (FGFR-1), insulin-like growth factor receptor 1 (IGFR-1), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), MET, and Sonic hedgehog (SHH) are also altered in glioblastoma [24,25]. The reason for such genetic diversity in glioblastomas is not clear.…”
Section: Diverse Nature Of Glioblastomamentioning
confidence: 99%
“…The study by Pećina-Šlaus et al indicated the increased expression of transcriptional factors TCF-1 and LEF-1 to be characteristic for malignant gliomas [23]. Other signaling pathways, including receptor tyrosine kinase (RTK), epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor A (PDGFRA), fibroblast growth factor receptor 1 (FGFR-1), insulin-like growth factor receptor 1 (IGFR-1), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), MET, and Sonic hedgehog (SHH) are also altered in glioblastoma [24,25]. The reason for such genetic diversity in glioblastomas is not clear.…”
Section: Diverse Nature Of Glioblastomamentioning
confidence: 99%
“…New approaches for enhancing cancer treatment by impairing cell migration and metastasis might offer promise for curing patients with malignancies. Combinations of anticancer therapeutic regimens that not only reduce cell proliferation but also limit metastasis would be advantageous (79).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins have potential as diagnostic, drug resistance, and invasiveness markers for glioblastoma tumors. Drug resistance is a major clinical problem in the treatment of many infectious diseases (Chowdhury et al, 2018;Hanif et al, 2017;Olar and Aldape, 2014). Proteomics shows solution for drug development against the resistance.…”
Section: Role Of Proteomics In Medical Microbiological Research and Dmentioning
confidence: 99%